2009
DOI: 10.1002/mus.21170
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation cramp threshold frequency correlates well with the occurrence of skeletal muscle cramps

Abstract: The minimum electrical stimulation frequency (HZ) at which a muscle cramps is termed threshold frequency (TF). TF is theorized to represent one's predisposition to cramping; however, TF and cramp occurrence have never been correlated. We hypothesized that TF would be lower in individuals with a cramp history and lower on the second of two days of testing; genetics may partially explain this lower TF. Cramp TF was measured in 19 subjects with (Group 1), and 12 subjects without (Group 2), a cramp history. Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
68
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 16 publications
7
68
1
7
Order By: Relevance
“…37 Prior studies suggest that threshold frequency is generally indicative of an individual's predisposition to muscle cramping. 37,38 Because of the lack of an effective therapy and high placebo response rates, there is confusion with regard to optimal therapy. The novel use of threshold frequency as a tool to quantitatively measure the response to various therapeutic interventions for muscle cramps is thus highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…37 Prior studies suggest that threshold frequency is generally indicative of an individual's predisposition to muscle cramping. 37,38 Because of the lack of an effective therapy and high placebo response rates, there is confusion with regard to optimal therapy. The novel use of threshold frequency as a tool to quantitatively measure the response to various therapeutic interventions for muscle cramps is thus highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…P ercutaneous electrical stimulation is a reliable and generally well-tolerated model for inducing muscle cramps and might be helpful for studying the pathogenesis and treatment of skeletal muscle cramps. 1,2 Most researchers studying electrically induced muscle cramps [1][2][3][4] have used a modification of the model described by Bertolasi et al, 5 who used trains of electrical stimuli consisting of 40 stimuli beginning at an initial electrical stimulation frequency of 1 Hz to induce cramps in the flexor hallucis brevis. Modifications to this technique include using an initial stimulation frequency of 4 Hz, increasing stimulation frequency in 2-Hz increments, and separating stimulations by 60 seconds of rest.…”
mentioning
confidence: 99%
“…Modifications to this technique include using an initial stimulation frequency of 4 Hz, increasing stimulation frequency in 2-Hz increments, and separating stimulations by 60 seconds of rest. [1][2][3] The minimum stimulation frequency at which a cramp occurs is termed threshold frequency (TF). In a previous investigation, we 3 reported that individuals with a history of muscle cramping have a lower TF than those who report no history of cramping.…”
mentioning
confidence: 99%
See 2 more Smart Citations